2008
DOI: 10.1111/j.1365-2036.2008.03860.x
|View full text |Cite
|
Sign up to set email alerts
|

Faecal microbiota profile of Crohn’s disease determined by terminal restriction fragment length polymorphism analysis

Abstract: SUMMARY BackgroundTerminal restriction fragment length polymorphism (T-RFLP) analyses are powerful tools to assess the diversity of complex microbiota. T-RFLPs permit rapid comparisons of microbiota from many samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 45 publications
2
44
0
Order By: Relevance
“…In fact, previous studies in our laboratory have shown that an elemental diet tended to modulate the gut microbiota profile in adult CD patients [41]. However, we could not evaluate the effects of the elemental diet in this study, since all of the CD patients were treated with it.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In fact, previous studies in our laboratory have shown that an elemental diet tended to modulate the gut microbiota profile in adult CD patients [41]. However, we could not evaluate the effects of the elemental diet in this study, since all of the CD patients were treated with it.…”
Section: Discussionmentioning
confidence: 64%
“…In our previous studies [17,40,41], the gut microbiota profiles of adult UC and CD patients during the active phase exhibited distinct patterns from those of healthy individuals [17,40,41]. However, these results might be influenced by serum anti-bacterial proteins (e.g.…”
Section: Discussionmentioning
confidence: 77%
“…Hence, intestinal inflammation in patients with CF could be correlated with increased enterobacterial counts. In addition, several studies concerning IBD pathology (1,9,34,57) and celiac disease (8) have reported increased Gammaproteobacteria levels. Bennet and coworkers (3) examined fecal microbial samples from very young infants during antimicrobial treatment and observed an increase of Enterobacteriaceae.…”
Section: Discussionmentioning
confidence: 99%
“…The paediatric studies suggest that higher effectiveness of nutritional therapy are observed in children with newly diagnosed CD (80%) in comparison with therapy of exacerbations of long-lasting disease (58%) [75].…”
Section: Nutrition As Therapeutic Management In Ibdmentioning
confidence: 99%
“…Moreover, nutritional therapy enables to maintain CD remission [69][70][71] and statistically significantly delays the need for surgical intervention or possible re-intervention [72]. Furthermore, numerous publications revealed that total enteral nutrition was associated with higher mucosal healing [73], changed intestinal microflora [74] and quicker weight gain [75], higher concentration of vitamin D [76], improved bone metabolism [77], increased insulin-like growth factor [78] and better quality of life after treatment [79], as compared to steroid therapy.…”
Section: Nutrition As Therapeutic Management In Ibdmentioning
confidence: 99%